A Novel Target Separation Algorithm Applied to The Two-Dimensional Spectrum for FMCW Automotive Radar Systems - Fei, Tai; Grimm, Christopher; Farhoud, Ridha; Breddermann, Tobias; Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE International conference on microwave, communications, anthenas and electronic systems)
In this paper, we apply a high-resolution approach, i.e. the matrix pencil method (MPM), to the FMCW automotive radar system to separate the neighboring targets, which share similar parameters, i.e. range, relative speed and azimuth angle, and cause overlapping in the radar spectrum. In order to adapt the 1D model of MPM to the 2D range-velocity spectrum and simultaneously limit the computational cost, some preprocessing steps are proposed to construct a novel separation algorithm. Finally, this algorithm is evaluated in both simulation and real data, and the results indicate a promising performance.

Hypothesis Test for the Detection of Moving Targets in Automotive Radar - Grimm, Christopher; Breddermann, Tobias; Farhoud, Ridha; Fei, Tai; Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE International conference on microwave, communications, anthenas and electronic systems (COMCAS))
In this paper, we present a hypothesis test for the classification of moving targets in the sight of an automotive radar sensor. For this purpose, a statistical model of the relative velocity between a stationary target and the radar sensor has been developed. With respect to the statistical properties a confidence interval is calculated and targets with relative velocity lying outside this interval are classified as moving targets. Compared to existing algorithms our approach is able to give robust classification independent of the number of observed moving targets and is characterized by an instantaneous classification, a simple parameterization of the model and an automatic calculation of the discriminating threshold.

Hidden Markov Model Variational Autoencoder for Acoustic Unit Discovery - Ebbers, Janek; Heymann, Jahn; Drude, Lukas; Glarner, Thomas; Haeb-Umbach, Reinhold; Raj, Bhiksha (INTERSPEECH 2017, Stockholm, Schweden)
Variational Autoencoders (VAEs) have been shown to provide efficient neural-network-based approximate Bayesian inference for observation models for which exact inference is intractable. Its extension, the so-called Structured VAE (SVAE) allows inference in the presence of both discrete and continuous latent variables. Inspired by this extension, we developed a VAE with Hidden Markov Models (HMMs) as latent models. We applied the resulting HMM-VAE to the task of acoustic unit discovery in a zero resource scenario. Starting from an initial model based on variational inference in an HMM with Gaussian Mixture Model (GMM) emission probabilities, the accuracy of the acoustic unit discovery could be significantly improved by the HMM-VAE. In doing so we were able to demonstrate for an unsupervised learning task what is well-known in the supervised learning case: Neural networks provide superior modeling power compared to GMMs.

Multi-Stage Coherence Drift Based Sampling Rate Synchronization for Acoustic Beamforming - Schmalenstroeer, Joerg; Heymann, Jahn; Drude, Lukas; Boeddeker, Christoph; Haeb-Umbach, Reinhold (IEEE 19th International Workshop on Multimedia Signal Processing (MMSP))
Multi-channel speech enhancement algorithms rely on a synchronous sampling of the microphone signals. This, however, cannot always be guaranteed, especially if the sensors are distributed in an environment. To avoid performance degradation the sampling rate offset needs to be estimated and compensated for. In this contribution we extend the recently proposed coherence drift based method in two important directions. First, the increasing phase shift in the short-time Fourier transform domain is estimated from the coherence drift in a Matched Filterlike fashion, where intermediate estimates are weighted by their instantaneous SNR. Second, an observed bias is removed by iterating between offset estimation and compensation by resampling a couple of times. The effectiveness of the proposed method is demonstrated by speech recognition results on the output of a beamformer with and without sampling rate offset compensation between the input channels. We compare MVDR and maximum-SNR beamformers in reverberant environments and further show that both benefit from a novel phase normalization, which we also propose in this contribution.

Detection of Moving Targets in Automotive Radar with Distorted Ego-Velocity Information - Grimm, Christopher; Farhoud, Ridha; Fei, Tai; Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE Microwaves, Radar and Remote Sensing Symposium (MRRS))
In this paper we present an algorithm for the detection of moving targets in sight of an automotive radar sensor which can handle distorted ego-velocity information. In situations where biased or none velocity information is provided from the ego-vehicle, the algorithm is able to estimate the ego-velocity based on previously detected stationary targets with high accuracy, subsequently used for the target classification. Compared to existing ego-velocity algorithms our approach provides fast and efficient inference without sacrificing the practical classification accuracy. Other than that the algorithm is characterized by simple parameterization and little but appropriate model assumptions for high accurate production automotive radar sensors.

Proceedings of the 2nd International Workshop on Resiliency in Embedded Electronic Systems

Second harmonic generation spectroscopy on hybrid plasmonic/dielectric nanoantennas - Linnenbank, Heiko; Grynko, Yevgen; Förstner, Jens; Linden, Stefan (Light: Science & Applications)
Keywords: tet_topic_opticalantenna; tet_topic_shg

Oblique incidence of semi-guided waves on step-like folds in planar dielectric slabs: Lossless vertical interconnects in 3D integrated photonic circuits - Hildebrandt, Andre; Alhaddad, Samer; Hammer, Manfred; Förstner, Jens (Integrated Optics: Devices, Materials, and Technologies XX)
Keywords: tet_topic_waveguide

Light scattering by ice crystals of cirrus clouds: From exact numerical methods to physical-optics approximation - Konoshonkin, Alexander; Borovoi, Anatoli; Kustova, Natalia; Okamoto, Hajime; Ishimoto, Hiroshi; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The problem of light scattering by ice crystals of cirrus clouds is considered in the case of a hexagonal ice plate with different distributions over crystal orientations. The physical-optics approximation based on (E, M)-diffraction theory is compared with two exact numerical methods: the finite difference time domain (FDTD) and the discontinuous Galerkin time domain (DGTD) in order to estimate its accuracy and limits of applicability. It is shown that the accuracy of the physical-optics approximation is estimated as 95% for the averaged backscattering Mueller matrix for particles with size parameter more than 120. Furthermore, the simple expression that allows one to estimate the minimal number of particle orientations required for appropriate spatial averaging has been derived.
Keywords: tet_topic_scattering

Comparison between the physical-optics approximation and exact methods solving the problem of light scattering by ice crystals of cirrus clouds - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Okamoto, H.; Sato, K.; Ishimoto, H.; Grynko, Yevgen; Förstner, Jens (22nd International Symposium on Atmospheric and Ocean Optics: Atmospheric Physics)
In the problem of light scattering by ice crystals of cirrus clouds, two exact methods (FDTD – finite difference time domain and DGTD – discontinuous Galerkin time domain) and the physical-optics approximation are used for numerical calculations of the Mueller matrix in the case of ice hexagonal plates and columns. It is shown that for the crystals larger than 10 μm at the wavelength of 0.532 μm the exact methods and physical-optics approximation closely agreed within three diffraction fringes about the centers of the diffraction patterns. As a result, in the case of random orientation of these crystals, the physical-optics approximation provides accuracy 95% for the averaged Mueller matrix.
Keywords: tet_topic_scattering

Phase sensitive properties and coherent manipulation of a photonic crystal microcavity - Quiring, Wadim; Jonas, Björn; Förstner, Jens; Rai, Ashish K.; Reuter, Dirk; Wieck, Andreas D.; Zrenner, Artur (Optics Express)
We present phase sensitive cavity field measurements on photonic crystal microcavities. The experiments have been performed as autocorrelation measurements with ps double pulse laser excitation for resonant and detuned conditions. Measured E-field autocorrelation functions reveal a very strong detuning dependence of the phase shift between laser and cavity field and of the autocorrelation amplitude of the cavity field. The fully resolved phase information allows for a precise frequency discrimination and hence for a precise measurement of the detuning between laser and cavity. The behavior of the autocorrelation amplitude and phase and their detuning dependence can be fully described by an analytic model. Furthermore, coherent control of the cavity field is demonstrated by tailored laser excitation with phase and amplitude controlled pulses. The experimental proof and verification of the above described phenomena became possible by an electric detection scheme, which employs planar photonic crystal microcavity photo diodes with metallic Schottky contacts in the defect region of the resonator. The applied photo current detection was shown to work also efficiently at room temperature, which make electrically contacted microcavities attractive for real world applications.
Keywords: tet_topic_phc

Light scattering by irregular particles much larger than the wavelength with wavelength-scale surface roughness - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We simulate light scattering by random irregular particles that have dimensions much larger than the wavelength of incident light at the size parameter of 𝑋=200 using the discontinuous Galerkin time domain method. A comparison of the DGTD solution for smoothly faceted particles with that obtained with a geometric optics model shows good agreement for the scattering angle curves of intensity and polarization. If a wavelength-scale surface roughness is introduced, diffuse scattering at rough interface results in smooth and featureless curves for all scattering matrix elements which is consistent with the laboratory measurements of real samples.
Keywords: tet_topic_scattering

Light scattering by ice crystals of cirrus clouds: comparison of the physical optics methods - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.; Grynko, Yevgen; Förstner, Jens (Journal of Quantitative Spectroscopy and Radiative Transfer)
The physical optics approximations are derived from the Maxwell equations. The scattered field equations by Kirchhoff, Stratton-Chu, Kottler and Franz are compared and discussed. It is shown that in the case of faceted particles, these equations reduce to a sum of the diffraction integrals, where every diffraction integral is associated with one plane–parallel optical beam leaving a particle facet. In the far zone, these diffraction integrals correspond to the Fraunhofer diffraction patterns. The paper discusses the E-, M- and (E, M)-diffraction theories as applied to ice crystals of cirrus clouds. The comparison to the exact solution obtained by the discontinuous Galerkin time domain method shows that the Kirchhoff diffraction theory is preferable.
Keywords: tet_topic_scattering

Discrete plasmonic solitons in graphene-coated nanowire arrays - Kou, Yao; Förstner, Jens (Optics Express)
e study the discrete soliton formation in one- and two- dimensional arrays of nanowires coated with graphene monolayers. Highly confined solitons, including the fundamental and the higher-order modes, are found to be supported by the proposed structure with a low level of power flow. Numerical analysis reveals that, by tuning the input intensity and Fermi energy, the beam diffraction, soliton dimension and propagation loss can be fully controlled in a broad range, indicating potential values of the graphene-based solitons in nonlinear/active nanophotonic systems.
Keywords: tet_topic_plasmonics; tet_topic_polariton

The role of electromagnetic interactions in second harmonic generation from plasmonic metamaterials - Alberti, Julian; Linnenbank, Heiko; Linden, Stefan; Grynko, Yevgen; Förstner, Jens (Applied Physics B)
We report on second harmonic generation spectroscopy on a series of rectangular arrays of split-ring resonators. Within the sample series, the lattice constants are varied, but the area of the unit cell is kept ﬁxed. The SHG signal intensity of the different arrays upon resonant excitation of the fundamental plasmonic mode strongly depends on the respective arrangement of the split-ring resonators. This ﬁnding can be explained by variations of the electromagnetic interactions between the split-ring resonators in the different arrays. The experimental results are in agreement with numerical calculations based on the discontinuous Galerkin time-domain method. (PDF) The role of electromagnetic interactions.... Available from: https://www.researchgate.net/publication/297612326_The_role_of_electromagnetic_interactions_in_second_harmonic_generation_from_plasmonic_metamaterials [accessed Aug 13 2018].
Keywords: tet_topic_shg; tet_topic_meta

Wave interaction in photonic integrated circuits: Hybrid analytical / numerical coupled mode modeling - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XX)
Typical optical integrated circuits combine elements, like straight and curved waveguides, or cavities, the simulation and design of which is well established through numerical eigenproblem-solvers. It remains to predict the interaction of these modes. We address this task by a ”Hybrid” variant (HCMT) of Coupled Mode Theory. Using methods from finite-element numerics, the optical properties of a circuit are approximated by superpositions of eigen-solutions for its constituents, leading to quantitative, low-dimensional, and interpretable models in the frequency domain. Spectral scans are complemented by the direct computation of supermode properties (spectral positions and linewidths, coupling-induced phase shifts). This contribution outlines the theoretical background, and discusses briefly limitations and implementational details, with the help of an example of a 2-D coupled-resonator-optical-waveguide configuration.
Keywords: tet_topic_waveguide; tet_topic_numerics

Offshore Metocean Station for Energy Purposes - Balluff, Stefan; Bendfeld, Jörg (Journal of Sustainable Development of Energy, Water and Environment Systems)

Ultrasonic transmission measurements in the characterization of viscoelasticity utilizing polymeric waveguides - Bause, Fabian; Rautenberg, Jens; Feldmann, Nadine; Webersen, Manuel; Claes, Leander; Gravenkamp, Hauke; Henning, Bernd (Measurement Science and Technology)
Keywords: material characterization; material parameters; acoustic waveguide; daming; ultrasonic transducer

Determination of the material properties of polymers using laser-generated broadband ultrasound - Claes, Leander; Meyer, Thorsten; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Journal of Sensors and Sensor Systems)

Miniaturized all-optical Sound Pressure Sensor - Fischer, Balthasar; Claes, Leander (INTER-NOISE 2016)